Child detachment as a correlate of social well-being of orphaned children in Ibadan and Abeokuta, Nigeria (2015)
This study investigated child detachment as a correlate of social well-being among orphaned children from selected orphanages in lbadan and Abeokuta. The study adopted a descriptive survey research design. A total of 350 respondents were purposively selected from the four orphanages using purposive sampling technique. The study found that the support and care received by the respondents have positive significant effects on their physical well-being and self-esteem. The study also showed that there is high prevalence of paternal death and loss of bread winners in households which has economic implication on the lives of the children. The findings showed that institutional care has beneficial effect on the lives of orphaned children especially in the urban setting as against the rural setting where extended family is still functioning. The study made some recommendations which include staff development training for proprietors and workers in orphanages to provide family-like environment for orphans in their custody.